THE IMPACT OF PHYSICAL-CHEMICAL CHANGES ON THE QUALITY OF FOOD HYDROGENATED FAT DURING STORAGE - Djuraeva Nafisa Radjabovna; Bakhtiyarov Sardorbek Bakhtiyarovich; Khafizova Manzura Nematovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
Modification of vegetable oils by hydrogenation is implemented in order to convert liquid vegetable oils into solid ones, while the selection of process conditions allows obtaining hydrogenated fats of varying degrees of hardness, which allows expanding their assortment and scope of application [1]. Vegetable oils are liquid in ordinary condition; therefore, many manufacturers use the method of hydrogenation in the presence of a catalyst to obtain a more solid consistency. During the hydrogenation process, hydrogen molecules are added to the oil to change the texture, stability, and increase the shelf life of the final product.